Framing the Role of Regional Actors in the Lebanese Sunni Politics: Perspectives from Sunni Groupings and Leaders - El Sayed, Moaz (Advances in Social Sciences Research Journal, 2023)
The aim of this article is to understand how Lebanese Sunni political actors construct their narratives on the role of Iran, Syria, and Saudi Arabia in the Lebanese Sunni politics and how those narratives are framed and counter framed. The article adopts Max Weber’s interpretivist or Verstehen research approach which emphasises that reality is a social construct. Using a case study research design with qualitative approach, the data is collected from the field employing interviews (semi-structured) and documents analysis. A purposive sampling technique was operationalised to choose 23 research participants including Sunni grouping leaders or representatives, politicians, Lebanese ministers, and members of Parliament (MPs) from various sides within the Lebanese Sunni political spectrum. The findings suggest that Iran appealed to various Sunnis by amplifying the frames of supporting Palestine, resisting Israel and countering western imperialism. Yet, some Sunnis frame Iran as deconstructing the Sunni politics and creating intra-Sunni friction. Syria’s role was framed by some Sunnis as 'divide-and-rule', claiming that Syria categorised Sunnis based on their association or lack thereof with them. Pro-Syrian Sunnis amplifies Syria’s perceived ‘pan-Arabism’ credential and contribution to ending Lebanese civil war. Saudi Arabia’s role in Lebanon is understood in the context of unifying Sunnis and integrating them into the Lebanese politics. The research recommends the Lebanese Sunnis to think globally and act locally in ways that will reestablish genuine democracy and development, placing the interest of Lebanon as the top priority.